Legal Liability of Beauty Product Business Owners for Overclaims on Products - Suisno; Muljono, Bambang Eko; Saputri, Nur Rahmah; Achmad Ausathuha (Universitas Islam Lamongan, 2025)
The beauty product industry in Indonesia is experiencing rapid growth which has also triggered the practice of overclaiming by business actors, namely excessive claims to the benefits or content of products without scientific basis. This practice misleads consumers and poses health risks, especially in skincare products. This research discusses two problem formulations: namely how the legal responsibility of business actors for the practice of overclaim, and how legal protection for consumers. This research uses normative juridical methods through statutory and conceptual approaches, the results of this study indicate that business actors can be held civilly, administratively, and criminally liable in accordance with the GCPL and BPOM regulations. Legal protection of consumers is carried out preventively, namely prevention efforts carried out before violations of consumer rights occur and repressive, namely a form of protection that includes dispute resolution, either through the court, the Consumer Dispute Resolution Agency (BPSK), or the provision of administrative and criminal sanctions to business actors who violate legal provisions.